O INCONSCIENTE POLÍTICO EM O AMANTE DE MARGUERITE DURAS - GODOY, DAYSE MARTINS DA COSTA (2018)
The following research has as objective the analysis of the book O amante (1990) by Marguerite Duras, which will be read in three different interpretation levels, whose fundaments are based on the theoretical perspectives of Fredric Jameson’s The Political Unconscious: Narrative as a Socially Symbolic Act (1992) and Roberto Schwarz’s Duas meninas (1997). In order to comprehend how Duras’ books were read by researchers from different areas, in the first chapter of this dissertation we recur to Marguerite Duras’ critical acclaim, so a political reading can be performed afterward. In the second chapter, we introduce the theoretical fundaments which base this research, in which we approach the memorialist writers’ characteristics, especially the elements of the autobiography. In the same chapter, Jameson and Schwarz’s theories are revised. Furthermore, the analysis is developed and organized in three different levels of reading. The first interpretative level, we comprehend the book as romantic writing when we analyze the aspects of this individual narrative, considering the report of a character who narrates her memories of adolescence in French Indochina. In the second level, we take the book as a rewriting of the historical discourse, verifying what the story tells us about the colonizers and natives’ social perspectives of French Indochina in the beginning of the twentieth century, as well as the battles fought by social classes where they act. In the third level of analysis, we consider the form as content by reading the narrative on the opposite perspective, which is presented as the text in which Duras not only talks about herself, but also about the situations that go beyond her, reaching the overcome of afflictions found in life through the writing.